What place for migrants from sub-Saharan Africa in the Maghreb? - (:unkn) unknown (My University, 2021)
The migration of sub-Saharan Africans often comes to the forefront of the media.Indeed, if migrations are part of the human geography of the Mediterranean basin, we have witnessed an increase in certain migratory movements in recent years. In this context, Maghreb countries are seeing their role change.Passing from the status of emigration country to that of host country, they sometimes find it difficult to adapt to this new position. Moreover, the action of the European Union, which is trying to turn them into places of detention in order to externalise the management of migrants, raises questions.In this article, we will therefore attempt to put forward a few lines of thought in order to better understand this migratory context which, beyond the media overexposure, still refers to complex and often desperate human situations.
Keywords: African Research